2002
DOI: 10.1021/jm020094i
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and SAR of Tachykinin Antagonists:  Modulation of Balance in NK1/NK2 Receptor Antagonist Activity

Abstract: Through optimization of compounds based on the dual NK(1)/NK(2) antagonist ZD6021, it was found that alteration of two key regions could modulate the balance of NK(1) and NK(2) potency. Substitution of the 2-naphthalene position in analogues of ZD6021 resulted in increased NK(1) potency and thus afforded NK(1) preferential antagonists. Alterations of the piperidine region could then increase NK(2) potency to restore dual NK(1)/NK(2) selectivity. Through these efforts, three novel receptor antagonists from a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…142 When the R 1 was hydrogen, cyclization occurred exclusively on the N-acryloyl group leading to 268b. 178 However, if the R 1 substituent was a methyl group, cyclization occurred predominantly on the N-allyl substituent yielding 268a. Detailed kinetic study on the substrate that had o-methyl group revealed that the inherently fast N-acryloyl cyclization was retarded at least by 2 orders of magnitude.…”
Section: Atropselective Reactionsmentioning
confidence: 99%
“…142 When the R 1 was hydrogen, cyclization occurred exclusively on the N-acryloyl group leading to 268b. 178 However, if the R 1 substituent was a methyl group, cyclization occurred predominantly on the N-allyl substituent yielding 268a. Detailed kinetic study on the substrate that had o-methyl group revealed that the inherently fast N-acryloyl cyclization was retarded at least by 2 orders of magnitude.…”
Section: Atropselective Reactionsmentioning
confidence: 99%
“…Therefore simultaneous antagonism of both NK 1 and NK 2 receptors have been investigated, by altering the two key regions, piperidine and naphthamide moieties in the dual NK 1 /NK 2 receptor antagonist 45 (ZD-6021) [259]. Substitution at 2-naphthalene position increases NK 1 potency while alterations in piperidine region increases the NK 2 potency.…”
Section: Non-peptide Antagonistsmentioning
confidence: 99%
“…Attempts to effect carbonylation of the iodide to give ester 19 were unsuccessful using a variety of methods, with protodehalogenation predominantly occurring. Eventually, carbonylation was successfully achieved in a sealed tube at 120 °C under a carbon monoxide atmosphere in the presence of palladium acetate and triethylamine …”
mentioning
confidence: 99%